Effect of fatigue in spatiotemporal parameters during 100 m front-crawlevent monitored through 3D dual-medial automatic tracking - Ribeiro, J.; Morais, S. T.; Figueiredo, P.; de Jesus, K.; Vilas-Boas, J. P.; Fernandes, R. J. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The purpose of the present study was to analyse the effect of fatigue on the three dimensional arm-stroke pattern during a 100 m front-crawl race. Six national level swimmers performed a 100 m front-crawl test at maximal intensity. The event was recorded with eight underwater and seven land cameras (Qualisys AB, Gothenburg, Sweden) using a full body retro-reflective marker setup. Swimming velocity, stroke frequency, stroke length, hand velocity, backward amplitude, amplitude slip, hand depth, width and range, and index of coordination were assessed for each 25 m lap. Differences between the four laps were analysed using a repeated measure ANOVA. Significant changes of analysed parameters were observed across the race, with exception of slip amplitude and hand depth, width and range. Thus, the analysis of spatiotemporal variables, under the influence of fatigue, should be understood as a relevant part of training monitoring aiming to increase performance, particularly when fatigue installs.